Masquelet-Induced Membrane Characteristics in Chicken Radii Bone Defects - Cueva, Luis O. B. [UNESP]; Rahal, Sheila C. [UNESP]; Fonseca-Alves, Carlos E. [UNESP]; Bonatelli, Shayra P. [UNESP]; Mamprim, Maria J. [UNESP]; Francia, Camila C. D. A. [UNESP]; Burini, Caio H. P. [UNESP]; Mesquita, Luciane R. [UNESP] (Assoc Avian Veterinarians, 2021)
This study evaluated the formation of a Masquelet-induced membrane created through the formation of segmental bone defects in the radii of 15 healthy domestic chickens. When the chickens were in a surgical plane of anesthesia, a 1.5-cm segmental bone defect was produced in the left radius, which was subsequently filled with a bone cement spacer during its pasty polymerization phase. The bone defects were evaluated through radiographic imaging immediately after surgery and at 7, 15, 21, and 30 days after the creation of the bone defect. Five birds were euthanatized at 15, 21, and 30 days postoperatively for histological evaluation of the bone defect site. Immediate postoperative radiographic examination of the radii showed the presence of bone cement, which occupied the segmental bone defect. Thirty days after the surgical procedure, the presence of new bone formation at the fractured extremities was evident in the 5 remaining chickens. Histologically, the induced-membrane had 3 distinct zones at 15 days postoperatively, including 1 cell layer in contact with the bone cement spacer, 1 layer with collagen fibers, and 1 layer in contact with muscle, which was composed of disorganized connective tissue, active fibroblasts, and blood vessels. Twenty-one days after surgery, the zones were less defined, and there were metaplastic areas comprising cartilage and bone. Postoperative, diffuse mineralization of the membrane was observed 30 days after the surgical procedure. Formation of the induced membrane was observed during all periods of evaluation. The best histological characteristics for the Masquelet-induced membrane were detected 15 days after the formation of the bone defect, suggesting this would be the optimal time for second-stage surgery for bone reconstruction.
Keywords: fracture; histology; bone cement; treatment; avian; chicken